Streptococcus spp. in Equines - Infection and Antimicrobial Susceptibility Profiles - Costa Torres, Mariana; Azevedo Moni, Camila; de Campos Menetrier, Luiza; Merker Breyer, Gabriela; Maboni Siqueira, Franciele (Acta Scientiae Veterinariae, 2022)
Background: Empirical antimicrobial prescribing is commonly used in equine veterinary. Therefore, professionals can obtain information about antimicrobial susceptibility profile of the bacterial strains based on veterinary literature. Considering equine infections, Streptococcus spp. are important pathogens that can cause serious damage in horses. Therefore, the aim of this study was to describe the antimicrobial susceptibility testing (AST) and infection profiles of Streptococcus spp. strains isolated from equines with infectious diseases subjected to microbiological analysis. Materials, Methods & Results: Veterinarians sent 13 samples and culture in Blood and MacConkey Agar were performed. After the incubation period, suspected colonies, which showed significative growth, were analyzed by Gram-staining, biochemical tests, and subjected to confirmatory identification in Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry. In vitro AST analysis were performed by disc diffusion method, in accordance with the veterinarians’ request. The antimicrobials tested in this study were: ceftiofur, gentamicin, ampicillin, enrofloxacin, amikacin, penicillin, trimethoprim-sulfamethoxazole, ciprofloxacin, doxycycline, vancomycin and metronidazole. The samples included uterine exudate, hock fistula, osteosynthesis exudate, exudate from the guttural pouch, and were originated from animals located in different and distant geographical regions in the cities of Porto Alegre, Pelotas, and Bagé, Rio Grande do Sul, Brazil. Streptococcus dysgalactiae, Streptococcus equi and Streptococcus thoraltensis were the Streptococcus species identified in the samples. S. dysgalactiae was the mainly species found in the uterus samples, while S. thoraltensis, an unusual Streptococcus species, was identified as etiological agent of endometritis in 2 of the analyzed animals. On the other hand, S. equi was found in both the guttural pouch, representing the etiological agent of the strangle case, and in the osteosynthesis exudate, as infectious agent of post-osteosynthesis surgery. The majority of streptococci strains were susceptible to ceftiofur drug. Amikacin and ciprofloxacin, however, were the drugs for which the strains were mainly resistant according to the results. Discussion: The present study provided the AST and infection profile of Streptococcus species related to equine infectious diseases. S. dysgalactiae is considered an unusual bacterium isolated from horses that can be related to endometritis, S. equi is the causative agent of strangles, and S. thoraltensis is unusual in equines. Generally, the observed susceptibility to ceftiofur of the strains analyzed was in agreement with previous results reported in the literature. However, ceftiofur is a third-generation cephalosporin and is considered a critically important antibiotic for human health and its use in veterinary medicine should be cautious. Considering the resistance profile found, Streptococcus spp. can be intrinsically resistant to low drug concentrations of aminoglycosides. Moreover, the emergence and spread of fluoroquinolones resistance may also be due to the acquisition of resistance via horizontal gene transfer. Therefore, the present study described both infection and antimicrobial susceptibility patterns of Streptococcus strains related to equine infectious diseases. Considering the findings, the results found in this study might contribute to the decision-making by veterinarians to further equine treatments. Keywords: antimicrobial susceptibility, pattern, AST, drug, resistant bacteria, horses, veterinarians.